Catalytic α‐Allylation of Enones with Alcohols via [Gold(I)]‐Mediated [3, 3]‐Sigmatropic Rearrangement of Propargylic Carboxylates. Issue 9 (18th April 2016) - Manoni, Elisabetta; Daka, Mario; Mastandrea, Marco M.; Nisi, Assunta De; Monari, Magda; Bandini, Marco
Abstract: The site‐selective α‐allylic alkylation of enones with alcohols via gold‐triggered formation of nucleophilic allenoates by means of [3, 3]‐sigmatropic rearrangements of propargylic carboxylates is reported. A range of α‐alkylated enones is obtained in high yields in the presence of the gold complex [JohnPhosAu(ACN)]SbF6 (2 mol%) as the promoting agent. Examples of allylation/Friedel–Crafts alkylation sequences are also provided, delivering densely functionalized dihydroindenes and dihydrobenzo[7]annulenes in a one‐pot procedure in moderate yields. The role of the Brønsted acidity (i.e., pivalic acid) delivered during the reaction course in assisting the formation of carbocationic intermediates is documented. Abstract :